Pengaruh Kepemimpinan Dan Kompetensi Pegawai Terhadap Kinerja Pegawai Melalui Kepuasan Pegawai di Lingkungan Bagian Protokol Biro Administrasi Pimpinan Sekretariat Daerah Provinsi Jawa Timur - Muhammad Ilham Arizal; Rudy Handoko; Achluddin Ibnu Rochim (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Government agencies such as BAPSD East Java are required to produce high employee performance. However, from performance assessment, BAPSD East Java performed Fairly. The aim of research to analyze the impact of Leadership and Competence on Employee Performance mediated by Job Satisfaction. This research was quantitative with the population of the Protocol Section of BAPSD East Java. The sample determination was through the Total Sampling technique so that the number of samples was 37 BAPSD East Java employees. The data collection technique was through a questionnaire with SEM PLS analysis. The results state Leadership and Competence had a significant impact on Job Satisfaction and Employee Performance. Job Satisfaction mediates the impact Leadership and Competence on Employee Performance.